Optimal design of a photovoltaic station using Markov and energy price modelling - Salazar Márquez, Marcio Boris (2023)
As the fight against anthropogenic global warming increases, photovoltaic (PV) systems, which are a type of renewable energy, are increasingly being considered. In order to use PV systems, it is necessary to develop methods to optimize their configuration, that is, the optimal number of PV modules and inverters. The objectives are to examine the optimization of PVs subject to not only the operational constraints but also the failure and repair events of PV inverters up to 100 kW, while minimizing the effective levelized cost of energy. To achieve this, using Markov modelling, a new energy price model that considers the current prices of the PV inverters is developed as part of a new optimization framework. A case study considering six real PV inverters is developed to show the effectiveness of the framework. In addition, real data from a reference PV station in Germany is used to calculate the average hours per day that a panel generates its rated power to consider the geographical location, temperature and number of sunny days in the given region. Unlike previous work, local and global optimal solutions are found using PV inverters in the range of 15 kW to 100 kW. Therefore, the new findings of this study will be considered in the future, for example, when considering the failure and repair events of PV modules.